Clindamycin microbial resistance in clinical isolates of Staphylococcus sp. derived from blood cultures of hospitalized patients - Amanda Cristina O. Silva; Ruan Carlos G. Silva; Sibele R. Oliveira
ABSTRACT Introduction: Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) strains have become common in hospitals, and this resistance has limited patients' treatment with beta-lactam antibiotics. Clindamycin is an important therapeutic agent for MRSA infections; however, inducible macrolide-lincosamide-streptogramin B (MLSB) resistance (iMLSB) has resulted in therapeutic failures with the use of this antimicrobial, with a consequent increase in patient mortality and length of stay. Objective: This study was carried out in order to detect phenotypes of inducible and constitutive resistance to clindamycin in blood culture samples of Staphylococcus sp. from hospitalized patients. Material and methods: A hundred bacterial samples from blood cultures of adult patients were evaluated, identified by conventional phenotypic tests, and subject to determination of susceptibility and resistance profiles with cefoxitin, erythromycin, and clindamycin discs; and to phenotypic evaluation of iMLSB resistance using the D-test. The results were interpreted in accordance with the recommendations of the Clinical and Laboratory Standards Institute (CLSI) 2014. Results: In this study, 65% of 60 bacterial strains were susceptible to cefoxitin and 35%, resistant. The constitutive MLSB (cMLSB) resistance phenotype was observed in 15.56% of the methicillin-sensitive Staphylococcus aureus (MSSA) samples, 33.33% of methicillin-sensitive coagulase-negative Staphylococcus (MSCONS), 26.67% of MRSA and 20% of methicillin-resistant coagulase-negative Staphylococcus (MRCONS), while iMLSB resistance was observed only in strains susceptible to cefoxitin, corresponding to 80% in MSSA and 20% in MSCONS. Conclusion: The D-test is a key test for the constant monitoring of the inducible resistance phenotype (which may impair the effectiveness of treatment with clindamycin), minimizing potential medication errors and adverse clinical outcomes.